A YOUNG GIRL WITH FITS - Ahmed, Imran; Ahmed, Ejaz; Zaidi, Badshah Hussain; Ansari, Jawad Khaliq; Nisar, Shazia (Journal of Ayub Medical College Abbottabad, 2015)
A young girl presented with fits vomiting and epigastric pain. Investigations including CT-Scan brain, MRI brain, MRV brain and cerebrospinal fluid (CSF) examination were normal. Her urine was screened for porphobilinogen which was positive. She responded to intravenous dextrose and hypercaloric diet Keywords: Porphyria,Porphobilinoge,Haeme arginate